2020
DOI: 10.1107/s1600576720013059
|View full text |Cite
|
Sign up to set email alerts
|

Application of precise neutron focusing mirrors for neutron reflectometry: latest results and future prospects

Abstract: Neutron reflectometry (NR) is a powerful tool for providing insight into the evolution of interfacial structures, for example via operando measurements for electrode–electrolyte interfaces, with a spatial resolution of nanometres. The time resolution of NR, which ranges from seconds to minutes depending on the reflection intensity, unfortunately remains low, particularly for small samples made of state-of-the-art materials even with the latest neutron reflectometers. To overcome this problem, a large-area focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…flooding), while being effective in resisting damage caused by fuel impurities [135]. Under low-RH conditions, changes in membrane properties (porosity, hydrophobicity, thickness) necessitate careful characterisation of the structure under operando conditions [136] in order to minimize Ohmic drop while managing the water content for optimal performance. Improvements in reflectivity instruments (e.g., RAINBOWS at ILL [72]) are set to open up new possibilities for operando studies of thin-film AEM membranes, while highlighting the evolution of interfacial structures, as has been demonstrated for electrode-electrolyte interfaces [135].…”
Section: Backbone Nanostructurementioning
confidence: 99%
“…flooding), while being effective in resisting damage caused by fuel impurities [135]. Under low-RH conditions, changes in membrane properties (porosity, hydrophobicity, thickness) necessitate careful characterisation of the structure under operando conditions [136] in order to minimize Ohmic drop while managing the water content for optimal performance. Improvements in reflectivity instruments (e.g., RAINBOWS at ILL [72]) are set to open up new possibilities for operando studies of thin-film AEM membranes, while highlighting the evolution of interfacial structures, as has been demonstrated for electrode-electrolyte interfaces [135].…”
Section: Backbone Nanostructurementioning
confidence: 99%
“…Researchers from RIKEN conducted amorphous nickel-phosphorus (Ni-P) plating, diamond cutting and polishing on the substrate surface, and coated supermirrors on the substrate. Consequently, they fabricated two-segment elliptical focusing supermirrors, which enhanced the illumination of small samples and increased the beam time efficiency (Takeda et al, 2016;Hosobata et al, 2017Hosobata et al, , 2019Yamada et al, 2020). Herb et al (2022) designed a prototype elliptic nested mirror optics coated with m = 4.1 polarized supermirrors, which demonstrated a high imaging figure of merit of 72%.…”
Section: Introductionmentioning
confidence: 99%
“…Maruyama et al fabricated Ni-C/Ti supermirrors with m = 3, m = 4, and m = 6.7 by ion beam sputtering, and they demonstrated that doping carbon atoms to the Ni layer suppressed the interface roughness and led to higher reflectivity than when using Ni/Ti supermirrors [4]. The neutron-focusing supermirrors deposited on the ultra-precision figured substrates were fabricated and proved to be effective [5][6][7]. The measured efficiency and signal-to-noise ratio during the process were dominated by neutron flux for the focusing devices, and the neutron flux was related to the value of m of neutron supermirrors, which is the central component of the focusing devices.…”
Section: Introductionmentioning
confidence: 99%